2016
DOI: 10.1186/s41118-016-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variations in infant and child mortality in West Africa: a geo-additive discrete-time survival modelling

Abstract: This study examines the residual geographical variations in infant and child mortality and how the different categories of the risk factors account for the spatial inequality in West African countries. To this end, we pooled data for 10 of the countries extracted from Demographic and Health Surveys and used the spatial extension of discrete-time survival model to examine how the variables exert influence on infant and child mortality across space. Inference was Bayesian based on the computational efficient MCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 47 publications
(66 reference statements)
2
23
1
Order By: Relevance
“…Nevertheless, such rates are still high in comparison to the United States and Canada, where the figures declined, during the aforesaid years, from 6.2 to 5.7, and from 4.9 to 4.4, respectively. This paper focuses on the modelling of child mortality risk trends across different geographical areas, with the purpose of contributing with the increasing international interest in modelling the spatial structure of such problem [6]- [9]. Within this line of research, Gayawan et al [6] [6] illustrated the regional variations of child mortality among ten West African countries, finding some clusters of higher child mortality in northwest and northeast Nigeria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, such rates are still high in comparison to the United States and Canada, where the figures declined, during the aforesaid years, from 6.2 to 5.7, and from 4.9 to 4.4, respectively. This paper focuses on the modelling of child mortality risk trends across different geographical areas, with the purpose of contributing with the increasing international interest in modelling the spatial structure of such problem [6]- [9]. Within this line of research, Gayawan et al [6] [6] illustrated the regional variations of child mortality among ten West African countries, finding some clusters of higher child mortality in northwest and northeast Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…This paper focuses on the modelling of child mortality risk trends across different geographical areas, with the purpose of contributing with the increasing international interest in modelling the spatial structure of such problem [6]- [9]. Within this line of research, Gayawan et al [6] [6] illustrated the regional variations of child mortality among ten West African countries, finding some clusters of higher child mortality in northwest and northeast Nigeria. In the same line of thought, Jimenez-Soto et al [7] [7] showed the disparities among child mortality across rural-urban locations and regions in Cambodia, and analogous findings, additionally including variations within inter and inintra regions, were made in Papua, New Guinea [8] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan African countries also registered remarkable decline since year 2000, but this progress was insufficient to reach the Millennium Development Goal (MDG 4) target of a two-third reduction in under-5 mortality rate by year 2015, and is unlikely, in the present state, to attain the sustainable development goal target of a neonatal mortality rate of 12 deaths per 1000 live birth by 2030. West African countries have been identified as the major contributors to child mortality in sub-Saharan Africa, recording more than double the case recorded in southern or northern Africa [1,2]. Apart from malnutrition, leading causes of death among young children in Africa, like in most developing countries, have been identified to include preterm birth complications, malaria and non-malaria febrile, pneumonia, birth asphyxia, HIV/AIDS, and diarrhea [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing interest in recent years to take into account the modelling of the geographical dimension of children mortality risk [6]- [9]. Gayawan et al [6] illustrated the regional variations on children mortality among 10 West African countries. They found some clusters of higher child mortality in northwest and northeast of Nigeria.…”
Section: Introductionmentioning
confidence: 99%